An environmental psychology model of sustainability in sport: the roles of sustainability consciousness, environmental awareness, and personal social responsibility - Barış Karaoğlu; Oğulcan Usuflu; Harun Genç; Bilgehan Pepe; Berat Koçyiğit; Mehmet Behzat Turan; İbrahim Dalbudak; Osman Pepe (Frontiers in Psychology, 2026)
Background Understanding the psychological processes associated with sustainable behavior has become a major focus of environmental psychology. Although sustainability consciousness is generally associated with environmentally responsible behavior, the psychological processes underlying this association in sport remain insufficiently understood, particularly among sport science students. Therefore, the present study examined the serial mediating roles of environmental awareness and personal social responsibility in the association between sustainability consciousness and sustainability in sport. Methods A cross-sectional correlational design was employed. The study included 521 undergraduate students enrolled in Faculties of Sport Sciences at six universities in Türkiye during the 2025–2026 academic year. Participants completed the sustainability consciousness scale, environmental awareness scale, personal social responsibility scale, and sustainability in sport scale. Serial mediation analysis was performed using Hayes’ PROCESS Macro (Model 6) with 5,000 bootstrap resamples. Prior to hypothesis testing, the assumptions required for regression analyses, including normality, multicollinearity, and the absence of influential cases, were examined and found to be satisfactory. Results Sustainability consciousness was positively associated with environmental awareness, personal social responsibility, and sustainability in sport. Multiple regression analyses indicated that sustainability consciousness was positively associated with sustainability in sport. The serial mediation analysis further showed that sustainability consciousness was positively associated with environmental awareness and personal social responsibility, environmental awareness was positively associated with personal social responsibility, and both environmental awareness and personal social responsibility were positively associated with sustainability in sport. The direct association between sustainability consciousness and sustainability in sport remained statistically significant after accounting for the proposed mediators, suggesting partial mediation. Bootstrap analyses further indicated statistically significant indirect associations involving environmental awareness, personal social responsibility, and the sequential pathway including both constructs, as none of the 95% bootstrap confidence intervals included zero. These findings support the proposed serial mediation model as a theoretically informed pattern of statistical associations rather than evidence of causal mediation. Conclusion The findings suggest that sustainability consciousness, environmental awareness, personal social responsibility, and sustainability in sport are statistically associated in a manner consistent with the proposed environmental psychology framework. By examining these constructs within a serial mediation model, the present study contributes to the environmental psychology literature by providing a theoretically grounded perspective on the statistical associations underlying sustainability-related orientations within the sport context. The findings also have practical implications for the development of sustainability education and environmental responsibility initiatives within Faculties of Sport Sciences and provide a foundation for future longitudinal and experimental research examining these associations.